Diagnostic Accuracy of Contrast-enhanced Flair Magnetic Resonance Imaging in Detecting Meningeal Abnormalities in Suspected Cases of Infectious Meningitis - Ashapurna Bhagawati; Lipee Nath Dhanowar; Rajesh Kr Dhanowar; Gargi Choudhury; Pronami Borah; Venkatesh Dharavath (International Journal of Scientific Research in Dental and Medical Sciences)
Background and aim: To determine the diagnostic accuracy of contrast-enhanced fluid-attenuated inversion recovery in the diagnosis of meningitis and compare it with contrast-enhanced T1 sequence, taking cerebrospinal fluid (CSF) analysis as the gold standard.Material and methods: Forty patients referred to the Department of Radiodiagnosis of Assam Medical College and Hospital (AMCH) with clinical symptoms of meningitis were subjected to Magnetic Resonance Imaging (MRI) examination of the brain with pre- and post-contrast sequences, including T1 and fluid-attenuated inversion recovery sequences. Cerebrospinal fluid (CSF) analysis reports were the gold standard and correlated with the MRI findings. Also, an attempt was made to identify patterns of leptomeningeal enhancement in various aetiologies of meningitis.Results: The post-contrast fluid-attenuated inversion recovery (PC FLAIR) showed a significantly higher sensitivity of 97.06% (95% CI: 84.67% to 99.93%) than the PC T1FS, which had a sensitivity of 76.47% (95% CI: 58.83% to 89.25%). The specificity for PC FLAIR was found to be 83.33% (95% CI: 35.88% to 99.58%), while for PC T1FS, it is 66.67% (95% CI: 22.28% to 95.67%) without significant difference in specificity between the two sequences. The diagnostic accuracy of the PC FLAIR sequence was 95.00%, compared to 75.00% for the post-contrast T1 fat suppression (PC T1FS) sequence in diagnosing meningitis.Conclusions: The PC FLAIR sequence outperforms the PC T1FS sequence regarding sensitivity, area under the curve, and diagnostic accuracy. Adding this sequence to the conventional sequence can optimize the early detection of abnormal meningeal enhancement.